Possibilities of Existence of a Third Force J In Between Action and Reaction Forces of Newton - Lal, Shobha; Joshi, Jitendra (International Journal of Computer Sciences and Engineering, 2018)
In this research paper, the spite of action and reaction forces in case of Newton’s third law of motion there is a third force which plays vital role in the sustainability of any body. This force makes able the body to resist its shape in spite of the existing intermolecular forces. As long as the angle of responding the applying forces increases, value of reactionary forces decreases even with its components. Macro and Micro spectrum of air particle spreaded in the Universe protect the body as a plasma layer, angle β, force F give burn a new magnitude of force Ј which is plays decisive role and may be taken as the guiding factor to save the physical structure of a body. Values of this J =K(F+β)n where K= is the repetition of the frequency ranging from the whole number domain. n is supposed as the number of trial of any strike of any magnitude of a variable force during a certain moment provided no additional lubricants or viscous material is supplied during the application of these action and reaction of the forces